THE EFFECTVITY OF BLENDED LEARNING IN EDUCATION AND TRAINING FOR TEACHERS OF YOUNG CHILDREN PROGRAM - ARLINA,; HATIMAH, IHAT; ABDULHAK, ISHAK; ARDIWINATA, JAJAT S.; L, DADANG YUNUS (International Journal of Psychosocial Rehabilitation, 2020)
Education and training using ICT and online-based in non-formal education, especially for Young Children Education teachers, becomes an innovative idea to respond the challenges in the digital age 4.0. If you look at the results of 2019's quality mapping conducted by PP-PAUD and Dikmas West Java, it showed that there were many teachers and Education staffs whose qualifications were not appropriate. It also showed that there was a lack of training to improve the competence of teachers and staff of Young Children Program (PAUD). This study examined the effectiveness of the application of Education and training for elementary level of PAUD teachers through blended learning. Literature review used was the conception of blended learning, training concepts and Learning Management System (LMS). The research approach used was Research and Development with the ADDIE model. Participants participated through face-to-face mode of training through blended learning. The results showed that the online education and training with blended learning was effective in producing competent graduates. It was proved by positive changes in the insights, knowledge and skills of the participants, as a positive impact of online learning integration that developed e-learning content in the form of: teaching, learning videos, assignments, discussion forums and final examinations.